2012
DOI: 10.1016/j.aim.2012.07.026
|View full text |Cite
|
Sign up to set email alerts
|

The Hall algebra approach to Drinfeld’s presentation of quantum loop algebras

Abstract: The quantum loop algebra Uv(Lg) was defined as a generalization of the Drinfeld's new realization of the quantum affine algebra to the loop algebra of any Kac-Moody algebra g. It has been shown by Schiffmann that the Hall algebra of the category of coherent sheaves on a weighted projective line is closely related to the quantum loop algebra Uv(Lg), for some g with a star-shaped Dynkin diagram. In this paper we study Drinfeld's presentation of Uv(Lg) in the double Hall algebra setting, based on Schiffmann's wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…They showed that U (X) is a topological bialgebra and then defined DU (X) as its reduced Drinfeld double. Meanwhile, Dou, Jiang and Xiao [9] defined the "double composition algebra" DC(X) of coh-X as the subalgebra of D(coh-X) generated by two copies of C(X), say C ± (X), together with the group algebra K. Proof. It has been mentioned in [9] that DC(X) = DU (X).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that U (X) is a topological bialgebra and then defined DU (X) as its reduced Drinfeld double. Meanwhile, Dou, Jiang and Xiao [9] defined the "double composition algebra" DC(X) of coh-X as the subalgebra of D(coh-X) generated by two copies of C(X), say C ± (X), together with the group algebra K. Proof. It has been mentioned in [9] that DC(X) = DU (X).…”
Section: 2mentioning
confidence: 99%
“…Meanwhile, Dou, Jiang and Xiao [9] defined the "double composition algebra" DC(X) of coh-X as the subalgebra of D(coh-X) generated by two copies of C(X), say C ± (X), together with the group algebra K. Proof. It has been mentioned in [9] that DC(X) = DU (X). By [5,Corollary 5.23], the subalgebra DU (X) is generated by u ± O( x) , x ∈ L together with the torus K. Note that each line bundle O( x) is exceptional in coh-X.…”
Section: 2mentioning
confidence: 99%
“…where the sum is taken over all the isoclasses [L] in coh X, and F L M,N denotes the number of subsheaves X of L such that L ∼ = N and L/X ∼ = M . Following [34] (see also [8]), we can define the (reduced Drinfeld) double Ringel-Hall algebra DH(X) of X which admits a triangular decomposition…”
Section: Double Ringel-hall Algebra Of X and Lusztig's Symmetriesmentioning
confidence: 99%
“…where DC(coh X) denotes the composition subalgebra of DH(X). We refer to [8,Thm. 5.5] for the precise definition of Ξ.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation